Let’s Stop Wasting Women’s Potential - Francis, Anne (Florence Bird) (Canadian Journal of Counselling and Psychotherapy, 2012)
Our society has failed to realize the implications of the modern life cycle of the majority of women — most girls will have a job for at least 25 years of their lives. They will require appropriate education to broaden their perspectives and to lessen cultural bias; they will need good occupational counselling and confidence in their ability to work successfully. And our society must take action to allow women their opportunities and their rights to adequate and equal pay for their work.